Laser Processing of Electrospun PCL Fiber Mats for Tissue Engineering. Issue 11 (November 2015) - Zernetsch, Holger; Kern, Alexander; Jäschke, Peter; Glasmacher, Birgit
Purpose: Processing technologies for cutting and joining electrospun fiber mats are required to produce complex three-dimensional (3D) structures, like a scaffold for heart valve tissue engineering. The ability to bond very thin porous sheets, thus forming a stable 3D geometry, offers completely new design strategies such as organ-shaped scaffolds with void chambers inside. In this study, solvent, glue and laser bonding are compared with regard to their retention force and practicability. Methods: For this purpose, samples were prepared by applying each bonding technique. In addition, two different ways of preparing the bonding site were investigated: a portion of mats were bonded by an L-joint and the others by a T-joint; then tensile testing was performed until tearing of the bonding occurred. Additionally, the edges of laser cut fiber mats were investigated in order to evaluate the influence of thermal effects of the laser beam and ongoing changes in pore structure. Results: It was found that laser cut fiber mats were slightly deformed due to thermal effects, but still had an open, porous structure at the site of the cut. Results also show that joining of fiber mats by laser led to the best bonding result with highest retention force. Application of solvent and glue led to a nonuniform and noncontinuous bonding with lower retention forces. Conclusions: A first proof of concept for a heart valve-shaped scaffold was created by laser bonding. Thus, the laser is an advantageous tool for post-processing fiber mats and produce complex 3D structures for different applications.